(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Introduction: In the Philippines, the act of making a rape joke is considered rude, inappropriate, and unacceptable and the ones making rape jokes are criticized for their behavior. As a presidential candidate, Mr. Duterte was forced to apologize for his rape joke during a campaign in 2016. However, in 2017, then newly-elected President Duterte uttered three rape jokes in three different public events and was defended by two kinds of apologists: Presidential Spokespersons and Pro-Duterte social media supporters. Objectives: This study explores how official and social media apologists defended the President through various positions that ascribed him the right to make rape jokes, the Filipino people as having the duty to accept rape jokes, and women as having the duty to accept being the object of rape jokes. Methods: Using a sample of official government statements and public Facebook posts, major storylines and positions in the defense were identified and the implications of these were discussed. Results: There were six ways that President Duterte was positioned as to have certain rights that justified his use of a rape joke. Individually and collectively, these ultimately provided President Duterte the right to make a rape joke while placing the duty on citizens to allow President Duterte to excuse his rape joke. Conclusions: Knowing how President Duterte and citizens were positioned to make and accept rape jokes would enable society to challenge these positions and construct counter-positions that will defend women against rape jokes.